Impact of the COVID-19 pandemic on the immunization of the Human Papillomavirus vaccine among children and adolescents aged 9 to 14 years in the Xingu – Pará (Research, Society and Development, 2021)
Introduction: The Cervical Cancer (CC) is the second most common type of cancer in the female population. Human Papillomavirus (HPV) is considered a factor with high oncogenic potential for the development of CC. Immunization against HPV is one of the most economical public health interventions to date. With the emergence of the COVID-19 pandemic, this prevention has been affected. To understand the seriousness and possible negative consequences of this pandemic on disruption to immunization services in the Xingu region, it is necessary to take stock of trends in immunization coverage before and during the pandemic. Objective: To analyze the impact of the COVID-19 pandemic on anti-HPV vaccine coverage in children and adolescents aged 9 to 14 years, in the Xingu region, with an emphasis on the municipality of Altamira-Pará. Methods: This is a descriptive, ecological time series study, conducted with secondary data on anti-HPV vaccine coverage. Results: The study identified that, in the Xingu region, there was a reduction in immunization in six of the nine municipalities in that region, during the pandemic by COVID-19. Conclusion: In 2019, the Xingu region did not reach the recommended vaccination target. In 2020, during the pandemic, the situation was further aggravated. It is noteworthy that vaccination against HPV has a long-term impact on reducing the incidence of CCU morbidity and mortality. Public health problem which is within the goals of control of chronic non-communicable diseases.